Endoscopic Approach for Major Complications of Bariatric Surgery - Moon Kyung Joo (Korean Society of Gastrointestinal Endoscopy, 2017)
As lifestyle and diet patterns have become westernized in East Asia, the prevalence of obesity has rapidly increased. Bariatric surgeries, such as Roux-en-Y gastric bypass (RYGB), sleeve gastrectomy (SG), and laparoscopic adjustable gastric banding (LAGB), are considered the first-line treatment option in patients with severe obesity. However, postoperative complications have increased and the proper management of these complications, including the use of endoscopic procedures, has become important. The most serious complications, such as leaks and fistulas, can be treated with endoscopic stent placement and injection of fibrin glue, and a novel full-thickness closure over-the-scope clip (OTSC) has been used for treatment of postoperative leaks. Stricture at the gastrojejunal (GJ) anastomosis site after RYGB or incisura angularis in SG can be managed using stents or endoscopic balloon dilation. Dilation of the GJ anastomosis or gastric pouch may lead to failure of weight loss, and the use of endoscopic sclerotherapy, novel endoscopic suturing devices, and OTSCs have been attempted. Intragastric migration of the gastric band can be successfully treated using various endoscopic tools. Endoscopy plays a pivotal role in the management of post-bariatric complications, and close cooperation between endoscopists and bariatric surgeons may further increase the success rate of endoscopic procedures.